The performance quality rating scale (PQRS): reliability, convergent validity, and internal responsiveness for two scoring systems. (February 2015) - Martini, Rose; Rios, Jorge; Polatajko, Helene; Wolf, Timothy; McEwen, Sara
Abstract Purpose: The performance quality rating scale (PQRS) is an observational measure of performance quality of client-selected, personally meaningful activities. It has been used inconsistently with different scoring systems, and there have been no formal publications on its psychometric properties. The purpose of this study was to test and compare the psychometric properties of two PQRS scoring systems in two populations. Methods: A secondary analysis of video recorded participant-selected activities from previous studies involving either adults living with stroke or children diagnosed with developmental coordination disorder (DCD) was conducted. Three pairs of raters scored the video recorded performances with PQRS operational definitions (PQRS-OD) and a generic rating system (PQRS-G). Results: For inter-rater reliability, PQRS-OD ICCs were substantial, ranging from 0.83 to 0.93; while the PQRS-G ICCs were moderate, ranging from 0.71 to 0.77. Test–retest reliability was substantial, >0.80 (ICC), for both rating systems across all rater pairs. Internal responsiveness was high for both rating systems. Convergent validity with the Canadian Occupational Performance Measure (COPM) was inconsistent, with scores ranging from low to moderate. Conclusion: Both scoring systems have demonstrated they are reliable and have good internal responsiveness. The PQRS-OD demonstrated greater consistency across raters and is more sensitive to clinically important change than the PQRS-G and should be used when greater accuracy is required. Further exploration of validity with actual rather than perceived performance measures is required. Implications for Rehabilitation The PQRS provides clinicians and researchers with a means of measuring actual performance of self-selected activities. Rehabilitation scientists are encouraged to improve our understanding of the relationship between perceived and actual performance as a means to improve interventions and outcomes.